2014
DOI: 10.1093/molbev/msu281
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Conformational Dynamics Determines the Conversion of a Promiscuous Generalist into a Specialist Enzyme

Abstract: β-Lactamases are produced by many modern bacteria as a mechanism of resistance toward β-lactam antibiotics, the most common antibiotics in use. β-Lactamases, however, are ancient enzymes that originated billions of years ago. Recently, proteins corresponding to 2- to 3-Gy-old Precambrian nodes in the evolution of Class A β-lactamases have been prepared and shown to be moderately efficient promiscuous catalysts, able to degrade a variety of antibiotics with catalytic efficiency levels similar to those of an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
140
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 75 publications
14
140
0
Order By: Relevance
“…It should be noted that the ancestral lactamases were experimentally characterized and demonstrated to be able to promiscuously catalyse the degradation of a range of antibiotics with activity levels that are similar to those of the average modern enzyme [84]. A combination of molecular dynamics simulations [101], with analysis through the 'Dynamic Flexibility Index' [102] (an approach which allows for the quantification of the contribution of each position in a protein to functionally related dynamics) showed clear changes in the conformational dynamics of the enzyme across evolutionary time. That is, while the active site of the modern lactamase was shown to be comparatively rigid, the ancestral lactamases showed much greater flexibility, in particular, in residues near the active site of the enzyme.…”
Section: B-lactamasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the ancestral lactamases were experimentally characterized and demonstrated to be able to promiscuously catalyse the degradation of a range of antibiotics with activity levels that are similar to those of the average modern enzyme [84]. A combination of molecular dynamics simulations [101], with analysis through the 'Dynamic Flexibility Index' [102] (an approach which allows for the quantification of the contribution of each position in a protein to functionally related dynamics) showed clear changes in the conformational dynamics of the enzyme across evolutionary time. That is, while the active site of the modern lactamase was shown to be comparatively rigid, the ancestral lactamases showed much greater flexibility, in particular, in residues near the active site of the enzyme.…”
Section: B-lactamasesmentioning
confidence: 99%
“…That is, while the active site of the modern lactamase was shown to be comparatively rigid, the ancestral lactamases showed much greater flexibility, in particular, in residues near the active site of the enzyme. Further principal component analysis of the conformational dynamics of these enzymes demonstrated that the ancestral b-lactamases form a cluster that is distinct from the more rigid modern TEM-1 lactamase [101]. An unrelated study by Vila and co-workers [103] employed NMR spectroscopy in order to explore the intrinsic dynamic features of different variants of a metallo-b-lactamase, metallo-b-lactamase II (BcII).…”
Section: B-lactamasesmentioning
confidence: 99%
“…Our systematic study of 34 families of enzymes showed that the correlations become even more pronounced when focusing on the mobilities in the global modes (3). In a series of studies, the dynamic flexibility index determined from ENMs as a measure of mobility is used to understand the sequence evolution and functional enhancement (52,(71)(72)(73).…”
Section: Future Directions: Bridging Structural Dynamics and Sequencementioning
confidence: 99%
“…These specific DFI patterns suggest that the protein's native state is actually an ensemble of conformations displaying the structural variability in the active site region required for efficient binding of substrates of different sizes and shapes. On the other hand, DFI analysis of modern TEM-1 lactamase shows a comparatively rigid active-site region, likely reflecting adaptation for the efficient degradation of a specific substrate, penicillin (43). Principal component analysis of the ancestral b-lactamases and the extant TEM-1 lactamase reveal the special dynamics associated with substrate promiscuity and is in agreement with the functional divergence, as the highest-order modes of the ancient b-lactamases cluster together, separated from their modern descendant.…”
Section: Introductionmentioning
confidence: 99%